Toward a preliminary research agenda for the circular economy adoption in Africa - Nijman-Ross, Elke; Umutesi, Jessie Umuhire; Turay, Joseph; Shamavu, David; Atanga, Winifred Awinpoya; Ross, David Lang (Frontiers in Sustainability, 2023)
Circular economy (CE) research plays an important role in accelerating the CE transition globally and is an essential tool to contribute to climate change adaptation. However, prior CE research is primarily focused on countries in the Global North, whereas CE research in the Global South has been largely unexplored, especially in African countries and contexts. Therefore, this study aims to develop a preliminary research agenda for CE development in African countries by identifying the current body of knowledge on CE, the existing CE research gaps and barriers to conducting CE research in African countries. This research applied a mixed method research design, whereby this study reviewed a total of 275 English and French articles from Google Scholar through a scoping literature review and carried out a quantitative and qualitative survey with 38 CE industry experts working on CE projects in African countries. The findings suggest that South Africa is the front-runner in CE research, with the most relevant publications and ongoing research projects conducted by CE experts. The dominant focus on CE research in South Africa is an urgent call for scholars to conduct country-specific research for additional African countries, especially since a significant part of the publications does not distinguish between countries. Based on findings, this study concludes that the current body of CE knowledge is primarily focused on one aspect of CE, circulating materials and products (keep products and materials in use), while there is consensus from published journal papers that there are meaningful gaps in other CE principles such as designing out waste and pollution and regenerating natural systems. Therefore, this paper suggests a list of research topics that can be further investigated. To the authors' knowledge, this study is the first attempt to establish a preliminary research agenda for CE across African contexts and countries.